Engineering for the circular economy: Upcycling of waste plastic materials from biological and health practices into carbon nanotubes - JAINABA CONTEH (2022)
Plastic pollution has led to environmental consequences which also impact the health of animals and humans. A systematic approach of dealing with plastic pollution is to introduce the waste materials into the circular economy by recycling, particularly recycling mixed plastics stream. Plastics being a source of carbons means that they can be used to produce carbon nanotubes (CNTs) through chemical vapour deposition. However, the solid state of the plastics must be altered to conform to the liquid delivery system of the chemical vapour deposition. It was determined that mixed plastics can be dissolved simultaneously used a sequential one-pot method firstly in m-cresol at 190 °C followed by the addition of toluene, which was then heated up to 160 °C. Dissolution experiments conducted at different temperatures were performed and the plastic precursors were injected into the CVD reactor using a steel needle. The benchmarking CNT growth conditions determined were gas flow at 1 L/min, catalyst concentration at 7.5% (w/w) and the temperature set at 950 °C. These conditions produced the greatest yield of carbon product. Characterisation of the CNTs produced were performed using Raman spectroscopy, scanning electron microscopy and thermogravimetric analysis. The averaged results obtained for the hydrocolloid, polyester, MF film and toluene/m-cresol precursors for product yield were 204 mg, 206 mg, 255 mg and 310 mg respectively; for G/D ratio were 1.21, 1.16, 1.25 and 1.16 respectively; and for mean CNT diameter were 64 nm, 68.7 nm, 65.8 nm and 62 nm respectively. It was concluded that the addition of plastics to toluene/m-cresol decreased yield but improved the quality of CNTs.